Geographic and other determinants of BMD change in European men and women at the hip and spine. a population-based study from the Network in Europe for Male Osteoporosis (NEMO). - Kaptoge, S; Reid, D; Scheidt-Nave, C; Poor, G; Pols, H; Khaw, K; Felsenberg, D; Benevolenskaya, L; Diaz, M; Stepan, J; Eastell, R; Boonen, S; et al. (2007)
INTRODUCTION: While the determinants of BMD change have been studied in women, there have been few longitudinal studies in men. As part of the Network in Europe for Male Osteoporosis (NEMO) study, data were analysed from 1337 men and 1722 women aged 50-86y (mean=67 years) from 13 centres across Europe to assess determinants of BMD change and between-gender contrasts. METHODS: BMD was measured at the femoral neck, trochanter and/or L2-L4 spine on 2 occasions 0.8-8 years apart (mean=3.5 years) using DXA densitometers manufactured by Hologic (n=6), Lunar (n=5) and Norland (n=2). Each was cross-calibrated using the European Spine Phantom and annual rates of BMD change (g/cm(2)/year) were calculated from the standardised paired BMD values. The EPOS risk factor questionnaire was administered at baseline. RESULTS: In multivariate linear regression models, there were large between centre differences in the mean rates of BMD change in all 3 sites for both genders (P<0.0001) with the standard deviation of the between centre heterogeneity in the adjusted means being 0.005 g/cm(2)/year at the femoral neck. The overall adjusted mean annual rates of BMD change in g/cm(2)/year (95% CI) pooled across centres by random effects meta-analysis in men were: femoral neck -0.005 (-0.009, -0.001); trochanter -0.003 (-0.006, -0.001); and spine 0.000 (-0.004, 0.004). In women the respective estimates were: -0.007 (-0.009, -0.005); -0.004 (-0.006, -0.003); and -0.005 (-0.008, -0.001). The I(2) statistic for heterogeneity was between 81% and 94%, indicating strong evidence of between centre heterogeneity. Higher baseline BMD value was associated with subsequent greater decline in BMD (P<0.001). Preserved BMD was associated with higher baseline body weight in all 3 sites in men (P<0.012) but not in women. Weight gain preserved BMD (P<0.039) in all 3 sites for both genders, except the male spine. Increasing age was associated with faster BMD decline at the trochanter in both genders (P<0.026) and with a slower rate of decline at the female spine (P=0.002). Effects of lifestyle, physical activity, medications, and reproductive factors were not consistent across sites or between genders. CONCLUSION: These results show major geographic variations in rates of BMD change in men and women over 50 years of age across diverse European populations and demonstrate that body weight and weight gain are key determinants of BMD change in men.